Sairee Chahal: For She's a Jolly Good SHERO!. Issue 1 (June 2019) - David, Sonali A.
Sairee Chahal is a serial entrepreneur and the founder of SHEROES. She has innovated pathways to build a favourable work ecosystem for women in India, relying heavily on technology to solve the problems of gender disparities in the workforce. SHEROES is a globally formidable platform, changing the game for women and their aspirations. Over a million women have directly benefitted. In this interview, Sairee speaks to Sonali David about SHEROES and the importance of technology in opening the workspace for women.